2008
DOI: 10.1007/s11524-008-9330-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Acquisition among Injecting Drug Users: A Cohort Analysis of a National Repeated Cross-sectional Survey of Needle and Syringe Program Attendees in Australia, 1995–2004

Abstract: High hepatitis C virus (HCV) prevalence has been documented among many injecting drug user (IDU) populations worldwide; however, there is limited published data on trends in incidence of infection in these epidemics over time. To address this, we used a novel method of analyzing data collected via repeat, cross-sectional sero-surveys by injection initiation cohorts to investigate trends in HCV seropositivity among a population of needle and syringe program (NSP) attendees in Australia between 1995 and 2004, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Studies frequently report associations between HCV infection and injection duration, injection frequency, cocaine injection, and sharing of syringes and other injection paraphernalia among persons who inject drugs (PWID; Boodram et al, 2010; Falster et al, 2009; Garfein et al, 1996; Hagan et al, 2001; Pouget et al, 2012; Thorpe et al, 2000). Recent trends show that although both HIV (Broz et al, 2014; Centers for Disease Control and Prevention, 2009) and HCV (Amon et al, 2008) prevalence have steadily declined among older PWID, high-incidence of HCV infection (Page et al, 2009; Zibbell et al, 2015) and HCV outbreaks among younger PWID (Centers for Disease Control and Prevention, 2011; Leuchner et al, 2008) are occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Studies frequently report associations between HCV infection and injection duration, injection frequency, cocaine injection, and sharing of syringes and other injection paraphernalia among persons who inject drugs (PWID; Boodram et al, 2010; Falster et al, 2009; Garfein et al, 1996; Hagan et al, 2001; Pouget et al, 2012; Thorpe et al, 2000). Recent trends show that although both HIV (Broz et al, 2014; Centers for Disease Control and Prevention, 2009) and HCV (Amon et al, 2008) prevalence have steadily declined among older PWID, high-incidence of HCV infection (Page et al, 2009; Zibbell et al, 2015) and HCV outbreaks among younger PWID (Centers for Disease Control and Prevention, 2011; Leuchner et al, 2008) are occurring.…”
Section: Introductionmentioning
confidence: 99%
“…HCV prevalence can reach 30% to 60% within a few years of its first appearance in a population of injection drug users and achieve greater than 90% in a mature epidemic (24)(25)(26)(27)(28). In this study, there was no history of injection drug users in patients with anti-HCV (+) and anti-HCV (-).…”
Section: Issn: 1309-5102mentioning
confidence: 71%
“…14,16,18 Prison NSPs operating in six European jurisdictions have had favourable results, with stable or decreased drug use and decreased reports of drug initiation, decreased equipment sharing and no reported cases of HCV, hepatitis B or HIV transmission. 19 Whereas HCV seroprevalence was higher among Indigenous participants, HIV seroprevalence rates were around 1% for both groups. Given this study has demonstrated higher risk behaviour associated with HCV seroprevalence, there is an urgent need for a heightened awareness among Indigenous PWID highlighting the risks of HIV transmission.…”
Section: Risk Behaviourmentioning
confidence: 97%